Animal health as a function of farmer personality and attitude: using the HEXACO model of personality structure to predict farm-level seropositivity for Fasciola hepatica and Ostertagia ostertagi in dairy cows - Leinmueller, Markus; Adler, Friedemann; Campe, Amely; Knubben-Schweizer, Gabriela; Hoedemaker, Martina; Strube, Christina; Springer, Andrea; Oehm, Andreas W. (Frontiers in Veterinary Science, 2024)
IntroductionInfections with Fasciola hepatica and Ostertagia ostertagi impinge upon dairy cow health and welfare and represent a major economic factor in livestock industry. Control measures largely rely on the use of anthelminthic drugs. However, reports of anthelmintic resistance necessitate sustainable approaches. Farmer characteristics such as attitude and personality are crucial for the implementation of control strategies and on-farm practices.MethodsIn the present study, the HEXACO (Honesty-Humility, Emotionality, eXtraversion, Agreeableness, Conscientiousness, Openness to experience) model of personality structure, which conceptualizes human personality, was used to evaluate the relationship of farmer aspects with on-farm bulk tank milk seropositivity for F. hepatica and O. ostertagi. Moreover, information on farm structure, housing, management, and farmers’ attitude was collected in a face-to-face interview. Farm-level seropositivity for F. hepatica and O. ostertagi was predicted via elastic net regression.ResultsOut of 193 farms housing 8,774 cows in the German Federal State of Bavaria, 47 farms (24.4%) were seropositive for F. hepatica, 77 farms (39.9%) for O. ostertagi, and 42 farms (21.8%) for both endoparasites. The model for F. hepatica seropositivity selected the covariates pasture access, O. ostertagi seropositivity, higher farmer conscientiousness, and organic farming as relevant predictors. Seropositivity for O. ostertagi was predicted by F. hepatica seropositivity, pasture access, organic farming, and farmers being neutral regarding their satisfaction with animal health on their farm. Higher values for the HEXACO factors extraversion and emotionality were inversely associated with O. ostertagi seropositivity.DiscussionThe present work emphasizes the importance of farmer traits in regard to animal health and parasite occurrence. For the effective acceptance and implementation of sustainable control strategies for livestock helminth infections, it is crucial to consider these aspects to holistically address the challenges of managing parasitic diseases. Moreover, tailored communication strategies can be developed incorporating the understanding of individual stockman characteristics and subsequently ensuring encouragement of stakeholders.